Irrigation Fluid Absorption during PCNL: Hematological and Electrolyte Consequences - Swetha Ramani C K; Geethu Sivan; Pushparani Anand; Karthik Kandan; Mirunalini Gunaseelan (Medical Science: Trends and Innovations Vol. 3, 2025)
Aim: Percutaneous Nephro Lithotripsy (PCNL) is considered one of the most effective treatment methods for renal and upper ureter calculi measuring >2cm but risk factors for increased irrigation fluid absorption and immediate changes in post-operative patient vitals and hematological profiles have not been identified as that of TURP. Hence the study was conducted to evaluate changes in post of vital parameters, complete blood count and serum electrolytes and their correlation to common factors which is known to affect fluid absorption Methodology: Thirty-three ASA class I & II patients aged between 18-65 years undergoing PCNL surgery were selected and pre-operative and post-operative heart rate, systolic and Diastolic blood pressure, Temperature, Complete blood count and serum electrolytes were recorded and compared using the student t-test. Correlation post-operative values with the total duration of surgery, total duration of irrigation, TVIRF volume and total intravenous fluid was found with Pearson’s correlation coefficient. Results: There were statistically significant changes in post-operative blood indices and electrolytes. Post-operative hemodynamic parameters DBP and TEMP had significant changes. Also, there was a significant correlation between these changes with total duration of surgery (TDS), total duration of irrigation (TDIR), total volume of intravenous fluid (TVIVF), and total volume of irrigation fluid (TVIRF) used. Interpretation and Conclusion: There is a statistically significant fall in blood indices, electrolytes and hemodynamic values with increased IRF absorption.